Effect of protein intake on the onset of puberty in Bunaji and Friesian x Bunaji crossbred bulls in Nigeria - Rekwot, P.I.; Oyedipe, E.O.; Akerejola, O.L.; Kumi-Diaka, J.; Umoh, J.E. (Elsevier, 1987)
The effect of two levels of protein intake on age, body weight, chest girth, withers height and condition score at puberty in Bunaji and Bunaji x Friesian bulls were examined. Scrotal circumference, volume and motility of semen from the bulls were also evaluated to determine onset of puberty in Bunaji and the crossbreds.